Children's aggressive and prosocial behavior in relation to war exposure: Testing the role of perceived parenting and child's gender - Keresteš, Gordana (Array, 2006)
The aim of the study was to investigate long-term effects of exposure to war on children’ s aggressive and prosocial behavior, and to examine the potential moderating roles of perceived parenting and child’ s gender, by employing a multi-informant research design. Data were collected on a sample of school-age children from Croatia and their homeroom teachers several years after the war in Croatia had ended. The results have shown that being exposed to stressful war events could have negative long-term effects on aggressive and prosocial behavior, for both boys and girls. However, such a negative effect was not found for all of the employed measures of child’ s behavior, especially for peer ratings. Generally, positive parenting was not able to protect children from negative effects observed, especially when aggression was concerned. However, for teacher-rated prosocial behavior protective role of parenting was found. Among the children who perceived parenting behaviors of their parents more positively, the amount of war exposure was not related to teacher-rated prosocial behavior, while for those who perceived their parents less favourably, a greater amount of war experiences was connected with lower teacher-rated prosocial behavior. Theoretical as well as practical implications of the results were discussed, emphasizing the need of the communities to protect children from both exposure to war violence and negative effects of such exposure.